Risk Management: Emerging critical issues during the hospital administration of drug therapy - Lucio, Mango; Rachele, Caroti; Sarmila, Dhakal; Marco, Croce (Journal of Public Health International, 2023)
Interruptions during pharmacological therapy in a hospital ward can be a source of error. We therefore considered two Operating Units of a hospital by asking the following questions: are the nursing staff who administer drug therapy at the set times able to do so with maximum concentration and without interruptions? If yes, how? If not, why and what for? Furthermore, are there organizational and non-organizational improvement strategies so that nurses are less interrupted during therapy and therefore do not cause adverse drug events that could cause harm to the patient? The results that emerged from the data analysis make us reflect considerably on how much interruptions during therapy are to be paid attention to as a problem to which solution proposals can be found.